Pregnancy Outcome after Multifoetal Sac Reduction to Twin in Higher Order Multiple Pregnancies (Bangladesh Journal of Obstetrics & Gynaecology, 2010)
Objective: The aim of the study was to evaluate maternal and foetal outcome after fetoreduction in higher order multiple pregnancy. Materials and methods: This descriptive study was conducted at the Infertility Care and Research Centre (ICRC), Dhaka between 2006 and 2009. In eleven (11) cases, multifoetal pregnancy reduction (MFPR) were performed and maternal and foetal conditions were analyzed. All patients got pregnant after fertility treatment. The procedure was done between 8-10 weeks of gestation except in one case which was done at 17 weeks. Transvaginal approach under spinal anaesthesia was adopted for intracardiac injection of potassium chloride till cessation of cardiac pulsation. Antibiotic, aspirin, antispasmodic and progesterone were used for all patients. Main outcome measures were uterine contraction, leaking membrane, bleeding, infection, abortion, gestational age and birth weight. Results: Out of these eleven patients eight patients delivered twins at 37 weeks and one patient delivered a set of twin at 34 weeks and their antenatal period was uneventful. Two patients had abortions, one of which was not related with the procedure. No perinatal death was reported among 18 babies. Each of the babies born had an average weight of 2.42 kg. There was no serious maternal complication except rise of temp in one patient. Conclusion: Fetoreduction can improve the chances of survival and can reduce perinatal morbidity of remaining fetuses and can reduce maternal distress without any adverse affect to mother and foetuses. Key words: Sac reduction; multiple pregnancy DOI: 10.3329/bjog.v23i2.4960 Bangladesh J Obstet Gynaecol, 2008; Vol. 23(2) : 56-60